Pomegranate seed extract reduces ischemia induced anxiety in male rats - Maryam Rafieirad; Hamid Abbaszadeh (Shahrekord University of Medical Sciences, 2017)
Introduction: Ischemia-associated depression and anxiety may occur due to brain damage caused by oxidative stress. A number of reports indicated that treatment with herbal plant extracts with antioxidant properties could lead to a significant reduction in Ischemic complications. The aim of this study was to evaluate the behaviors of ischemic rats through animal models of anxiety and exploratory behavior (open field) to determine the efficiency of pomegranate seed extract (PGSE) as antioxidant. Methods: In this study, 21 male Wistar rats (250 ± 20 g) were randomly divided into 3 groups with 7 in each: 1) Control; 2) Ischemic; 3) Ischemic plus PGSE (14 days). In order to create ischemia/hypoperfusion, carotid arteries were ligatured and cut bilaterally. Then, plus maze and open-field tests were used for the measurement. Results: Ischemic rats showed a significant increase in anxiety or decrease approach and reduction locomotor activity compared to control group. Fourteen days administration of PGSE significantly improved the immobilization and ischemia-induced anxiety. Conclusion: PGSE exhibits therapeutic potential for anxiety and depression, which is most likely related, at least in part, to its antioxidant and free radical scavenging actions.